Maslahah Mursalah sebagai Salah Satu Metode Istinbath - Prahasti Suyaman (KRTHA BHAYANGKARA, 2024)
The development of human life always produces new things, for Muslims these new things require legal clarity. Many of the legal needs of Muslims are not listed directly in the main sources of law, namely the Quran and hadith, so ijtihad is required to complete them. There are several ijtihad methods that can be used and known by the majority of scholars and one of them is maslahah mursalah. This article will discuss the legal basis of maslahah, various types of maslahah, the views of scholars who are pros and cons to maslahah mursalah, and the hujjah of maslahah mursalah. Maslahah mursalah as a method of law-making is widely used to produce legal products related to human benefits